Olive trees in the world: past and present with future perspectives - Chacon-Ortiz, Andrés; Maia, Luciano Carlos da; Oliveira, Antônio Costa de; Perruolo, Gustavo; Pegoraro, Camila (Revista de Ciências Agroveterinárias, 2024)
The cultivation of the olive tree is of great economic importance worldwide. For the 2022-2023 harvest, were produced around 3,010,000 Mg of olive oil and 2,955,500 Mg of table olives of selected varieties, managing to establish itself in approximately 56 countries with different environments. In most of the cultivated areas only monovarietals were used, but mixtures of varieties have been recommended, which act as pollinators, avoiding reproduction problems. Furthermore, global warming also affects production efficiency and the quality of derived products. The olive grove underwent important changes due to genetic improvement. However, despite modern molecular tools, most of the work continues to be based on agronomic classical methods such as crossing and selection in progeny, delaying the development of new varieties. Models with high resolution climate projections are being used, allowing predicting the future evolution of the olive tree. Unfortunately, Brazil produces only 0.2% of its internal consumption and therefore has become the world's second largest importer after the United States to cover the growing demand. Based on this information, this review aims to discuss the adjustments in olive growing, which has been gaining more and more areas dedicated to its cultivation in Brazil.